Surgical Repair of Recto-Vaginal Tear from Dystocia in a Thoroughbred Mare: A Case Report - Malapolu, Shantha Vardhan; Maribasaviah, Dinesh Nanjappa; Adsul, Manojkumar; Jayanna, Renukaradhya Gudepalya; Sali, Abhilash Babu (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Rectovaginal fistula (RVF) is an abnormal communication  between the rectum and vagina, often resulting from  foaling trauma in mares, such as dystocia caused by  malpositioned foals (Pooniya et al., 2019). The injury is  seen predominantly in primiparous mares and is usually  due to violent expulsive efforts by the mare (Colbern et  al., 1985; Turner and McIlwraith, 1989). This condition risks  reproductive tract infections, potentially impairing fertility,  a critical concern for Thoroughbred breeding farms (LeBlanc,  2010). In India, where Thoroughbreds are bred under live cover regulations and tropical conditions, RVF management  is vital to minimize economic losses (Scoggin et al., 2015).  Surgical repair, typically using layered suturing, is the  standard treatment, with reported high success rates (Easley,  1988; Jalim and McKinnon, 2010). This case report describes  the successful surgical correction of a recto-vaginal tear in a  primiparous Thoroughbred mare from stud farm, Karnataka,  aiming to highlight effective management strategies and  their relevance to India’s equine industry.
Keywords: Surgical repair; management strategies; prolonged straining; faecal contamination